Quantum entrapment and valence charge polarization in Ag, Cu, Pt, and Rh nanoclusters - Ahmadi, Shideh (2016)
Atomic under-coordination and non-bonding electrons are extensively used in nanomaterials and nanostructures. The bonds between the under-coordinated sites follow the rule of relaxation dynamics, although quantum confinement (QC) theory, Coulomb blockade, and size-dependent dynamic effects cannot describe the change in Hamiltonian and other magnitudes. The effect of under-coordinated atom on the electronic structures of nanomaterials was calculated in this study using the bond-order-length-strength (BOLS) correlation and non-bonding electron polarization (NEP) notations. The Hamiltonian perturbation of the atomic under-coordination entrapped the core electrons and polarized the valence charge. Consistency between the BOLS-NEP notation and density functional theory (DFT) calculations on Ag, Cu, Pt, and Rh nanoclusters with cuboctahedral (COh) and Marks decahedral (M-Dh) structures confirmed that the shorter and stronger bonds between atomic under-coordination induced local densification, quantum entrapment, and valence charge polarization. The strong localization determined the intriguing catalytic, magnetic, and plasmonic attributes of these metallic nanoclusters. The effect of excess charge states from (+2) to (-2) was determined using DFT calculations and BOLS correlation theories on the metallic nanoclusters with COh and M-Dh structures. Consistency between DFT calculations and experimental observations confirmed our BOLS predictions including the local bond length relaxation, charge densification, quantum entrapment, valence band polarization, and magnetization of the metallic nanoclusters with negative, neutral, and positive excess charge states. Magnetization behavior was observed in the even (positive/negative) excess charge states for all metallic nanoclusters and the odd (positive/negative) excess charge states in the Pt and Rh nanoclusters. By contrast, non-magnetization behavior was observed in the odd (positive/negative) excess charge states in the Ag and Cu nanoclusters. Furthermore, Rh and Pt were regarded as donors and acceptors in the catalytic reactions, respectively. This work elucidated the development of cationic, neutral, and anionic metallic nanoclusters for catalyst and magnetic applications.